2011
DOI: 10.1002/hep.24649
|View full text |Cite
|
Sign up to set email alerts
|

An expanding role for primary care providers in the treatment of hepatitis C virus infection in the community

Abstract: Deming P, Kalish-man S, Dion D, et al. Outcomes of treatment for hepatitis C virus infection by primary care providers. N Engl Abstract The Extension for Community Healthcare Outcomes (ECHO) model was developed to improve access to care for underserved populations with complex health problems such as hepatitis C virus (HCV) infection. With the use of video-conferencing technology , the ECHO program trains primary care providers to treat complex diseases. We conducted a prospective cohort study comparing treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…lack of referral, centralization of treatment within tertiary care) . However, many of these factors are modifiable and potentially alleviated by integrated models of HCV treatment and care that move beyond hospital‐based specialist clinics .…”
Section: Discussionmentioning
confidence: 99%
“…lack of referral, centralization of treatment within tertiary care) . However, many of these factors are modifiable and potentially alleviated by integrated models of HCV treatment and care that move beyond hospital‐based specialist clinics .…”
Section: Discussionmentioning
confidence: 99%
“…The number of treated persons will even be lower because not every specialist is certified to provide HCV treatment and not all patients are eligible for treatment. Earlier studies have indicated that it is important to increase awareness among GPs concerning HCV treatment and referral possibilities [18], [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, successful strategies to improve engagement with HCV services and enhance HCV assessment have been explored. 21 One model to enhance access to HCV care for underserved populations focused on the integration of community-based health centers in New Mexico using state-of-the-art telehealth technology to provide training and support for primary care providers to deliver best-practice HCV care. 87 This model was effective, with similar responses to HCV treatment observed among community-based clinics as compared with a university-based hospital.…”
Section: How Can We Currently Prevent People With Hcv Infection From mentioning
confidence: 99%